Analisis Kinerja Jaringan Komputer Pada Topologi Star Dan Ring Dengan Protokol Routing Ospf (Kasus PT. Indonesia Comnets Plus Sbu Semarang) - Arif Budi Setiawan; Sri Eniyati (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to analyze the performance of the star and ring networks at PT Indonesia Comnet Plus SBU Semarang and then provide solutions to optimize the use of existing resources through network performance analysis using the OSPF routing protocol. The system development method that the author uses is prototyping. The initial stage begins with OSPF analysis carried out by researchers, then continues by using Wireshark to analyze network packets. After that, researchers will identify problems that occur on the network and provide solutions to fix them. Next, the solution designed by the researcher will be implemented on Cisco Packet Tracer. The testing method used in this research is network performance testing. Researchers conducted tests to verify whether the implemented solutions succeeded in improving network performance. The test results from this research are that the overall average delay in this design is 94.21 ms which is in the very good category, the overall average jitter in this design is 74.64 ms which means it is in the good category, the overall average throughput in this design it is 5.44 Kbps which is in the very good category, and the overall average packet loss in this design is 0% which means it is in the very good category.